Pendampingan Legalitas UMKM Desa Besowo, Kecamatan Kepung, Kabupaten Kediri - Hajril, M.; Nusantara, M.Billah Jaya; Rauf, Abdur; Nurlia, Siti; Abdullah, Khairunnisa; Sidiq, Muhammad Said (Aktualisasi Pengabdian Masyarakat, 2023)
The presence of business legality is a fundamental aspect in any enterprise. Business legality serves as a standard that all business practitioners, including those operating small-scale businesses like MSMEs, must meet to have their businesses legally recognized. However, legal aspects of businesses are often overlooked by many business operators, including those in the MSME sector. This serves as the background for the development of the "MSME Legal Support Program" conducted by students from the Collaborative Community Service Program Collaborative 84, hailing from UIN Sunan Kalijaga Yogyakarta, IAIN Kediri, UIT Lirboyo, and IAIFA Sumbersari. The program employs the ABCD method and is carried out through observation, interviews, and focus group discussions. The support activities commence with observations of MSME practitioners and are followed by coordination with village officials. The results of the program include enhancing the understanding of MSME practitioners regarding the importance of business legality and the issuance of NIB The long-term impacts of this program encompass the issuance of NIB, which can open up opportunities for collaboration with relevant agencies, as well as grant access to funding sources through government MSME programs. Additionally, this support program forges collaborations with advisors from the Ministry of Cooperatives and Small and Medium Enterprises, with the aim of streamlining the business legality registration process for MSMEs in Besowo Village in the future.